PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA TOKO RETAIL BAHAN-BAHAN BANGUNAN DI KECAMATAN DUNGKEK - Ahmad Ghufrony (Fakultas Ekonomi dan Bisnis, 2016)
The purpose of this research is to examine and analyze the influence of service quality toward customer’s satisfaction, the influence of price level toward customer’s satisfaction; the influence of customer’s satisfaction toward customer’s loyality; and the influence of price level toward the customer’s loyality of store of building materials at Dungkek subdistrict. The approach of this research is explanatory research. Researcher used 100 respondents as the sample of this research, which applied purposive sampling as the technique of sample collection. Researcher also used Partial Least Square (PLS) to analyze the data.Based on the result of this research, there are some conclusions: (1) service quality significantly influences customer’s satisfaction; (2) price level significantly influences customer’s satisfaction; (3) customer’s satisfaction has significant influence toward customer’s loyality; (4) service quality significantly influences customer’s loyality; and (5) price level significantly influences customer’s loyality.One practical implication of this research is that in order to improve the business competitiveness, especially in store of building materials, continuous improvement of service quality is needed,which can be done by adapting the given service quality with expected result from customer. The better service quality which is given, the higher chance that customer will do the next transaction or that customer will be a potential customer who may give positive recommendation to other people. Price level factor also positively influences customer’s satisfaction and loyality because it is a necessity for retailers of bulding materials store to pay attention to price level issue in order to improve the customer’s satisfaction and loyality. Policies in determining price level will give a certain satisfaction level to customers. The determined price should be equal with what is given by retailers and must be competitive. Therefore, customer’s satisfaction and loyality will increase.Keywords: Service quality, price level, customer’s satisfaction, customer’s loyality.